Pengaruh Profitabilitas, Struktur Modal, Ukuran Perusahaan, Kepemilikan Manajerial Dan Covid-19 Terhadap Nilai Perusahaan - Noorma Widiyaningrum; Triyono (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the influence of profitability, capital structure, firm size, managerial ownership, and the covid-19 pandemic on the firm value of property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2023. The research employs a quantitative method with an associative approach, analyzing the relationships between variables using multiple linear regression. Secondary data is collected from annual financial reports accessed through www.idx.co.id and the companies' official websites. The results indicate that profitability, capital structure, and firm size significantly affect firm value, while managerial ownership does not. Additionally, the study finds that COVID-19 has a significant impact on firm value. This research has limitations related to the data period (2020-2023) and its focus solely on the property and real estate sector. Future studies are recommended to extend the observation period and broaden the population and sample.